2016
DOI: 10.1055/s-0036-1583301
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Site Morbidity Following Free Tissue Harvest from the Thigh: A Systematic Review and Pooled Analysis of Complications

Abstract: Background Donor-site morbidity significantly influences patient satisfaction and quality of life following reconstructive surgery. The relevant donor-site morbidities associated with more commonly utilized thigh-based flaps are reviewed. Methods A systematic search of the MEDLINE and Cochrane databases from 1994 to 2014 was conducted to identify all reports of "anterolateral thigh (ALT)," "vastus lateralis (VL)," "anteromedial thigh (AMT)," "transverse upper gracilis (TUG)," tensor fascia latae (TFL)," "graci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 36 publications
0
36
1
1
Order By: Relevance
“…The transferred tissue has to provide a sufficient blood perfusion in order to avoid infections or unstable scar formation, and to facilitate wound healing as well as a good functional outcome (Hirche et al, ; Xiong et al, ). In clinical practice, vascularized flaps meet these requirements but are burdened with size limitations and donor site morbidity (Lakhiani, DeFazio, Han, Falola, & Evans, ; Lee & Mun, ; Paro, Chiou, & Sen, ; Seidenstuecker et al, ). Moreover, in the case of large burn injuries or extensive trauma, donor sites for free flaps are scarce in general.…”
Section: Introductionmentioning
confidence: 95%
“…The transferred tissue has to provide a sufficient blood perfusion in order to avoid infections or unstable scar formation, and to facilitate wound healing as well as a good functional outcome (Hirche et al, ; Xiong et al, ). In clinical practice, vascularized flaps meet these requirements but are burdened with size limitations and donor site morbidity (Lakhiani, DeFazio, Han, Falola, & Evans, ; Lee & Mun, ; Paro, Chiou, & Sen, ; Seidenstuecker et al, ). Moreover, in the case of large burn injuries or extensive trauma, donor sites for free flaps are scarce in general.…”
Section: Introductionmentioning
confidence: 95%
“…Depending on the site and size of the defects, as well as on properties of the flap, such as tissue composition and vascular supply [6], there are various autologous grafts that are currently used for transplantation, e.g., parts of the fibula, scapula, or the gastrocnemius muscle. However, the harvesting procedure creates an additional surgical site and can be associated with donor site morbidities such as loss or impairment of function, infection, swelling, contour deformities, and pain [7]. A further drawback of autologous transplants is the fixed shape of the grafts.…”
Section: The Technical Challenge: Reconstruction Of Large-scale Tissumentioning
confidence: 99%
“…In western countries, the ALT flap is most commonly used because harvesting of the tissue is a relatively simple procedure and the vascular anatomy is predictable. A recent systematic review demonstrated that an ALT flap is well‐tolerated by the majority of patients, even after taking into account some minor complications …”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review demonstrated that an ALT flap is well-tolerated by the majority of patients, even after taking into account some minor complications. 4 Postoperative mechanical bowel obstruction caused by impaired intestinal motility is a rare but potentially unavoidable complication after any type of abdominal surgery, 5 including in the setting of an additional abdominal procedure to harvest a free jejunum graft or to pull up the stomach for defected site after pharyngolaryngectomy. Such donor-site complications can result in prolonged hospitalization and excessive healthcare utilization, and, thus, increased medical and economic burdens on the patient.…”
Section: Introductionmentioning
confidence: 99%